1977
DOI: 10.1073/pnas.74.4.1729
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum sex hormones and glucose, insulin and lipid abnormalities in men with myocardial infarction.

Abstract: Fifteen patients who had had a myocardial infarction before the age of 43 were compared with thirteen age-matched normal subjects. Twelve of the patients and three of the controls had a delayed glucose and insulin peak in the glucose tolerance test. Curves with delayed peaks defin larger mean glucose and insulin areas than normal curves. When the measurements of the four patients with the largest areas under the glucose tolerance curve were separated, significant correlations were observed in the remaining pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
5

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 29 publications
5
42
0
5
Order By: Relevance
“…These correlations further support the possibility that hypotestosteronemia may be a prospective factor for MI as well as the hypothesis that risk factors for MI may be linked by an underlying alteration in the sex hormone milieu. 2 -3 In the present study and as found previously, testosterone correlated negatively with PAI-1 27 ' 37 and insulin 2 …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These correlations further support the possibility that hypotestosteronemia may be a prospective factor for MI as well as the hypothesis that risk factors for MI may be linked by an underlying alteration in the sex hormone milieu. 2 -3 In the present study and as found previously, testosterone correlated negatively with PAI-1 27 ' 37 and insulin 2 …”
Section: Discussionsupporting
confidence: 76%
“…When the patient group was successively reduced to a final study group of 34 men by excluding the patients with other major disorders, the testosterone and free testosterone correlations persisted (r=-.43, P<.02 and r=-.62, /><.001, respectively). Neither estradiol nor the risk factors, except for T he observations in men of hyperestrogenemia after myocardial infarction (MI), 1 of an association of sex hormones with risk factors for MI, 2 ' 3 and of a concurrence of risk factors for MI in clinical states other than MI and in populations 24 led to the hypothesis that an elevation in the estradiol-to-testosterone ratio or some closely related hormonal alteration may underlie risk factors and that hyperestrogenemia may lead to MI in men. 2 ' 3 Most laboratories studying sex hormones and MI in men have reported a high estradiol level after MI, both acutely 59 and months to years later.…”
Section: The Association Of Hypotestosteronemia With Coronary Artery mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1967, Avogaro et al described six obese patients with diabetes, hypercholesterolaemia, and marked hypertriglyceridaemia, all of whom improved on a hypocaloric and low-carbohydrate diet [3]. In the 1970s, Phillips suggested associations of aging, obesity and sex hormone-associated clinical manifestations with heart disease [4,5]. In the late 1980s, Reaven proposed insulin resistance as the critical factor and coined the name syndrome-X [6].…”
mentioning
confidence: 99%
“…In the 1970s, for the first time, Haller [3] used the term "metabolic syndrome" (MetS) for associations of obesity, diabetes mellitus (DM), hyperlipoproteinemia, hyperuricemia, and hepatic steatosis when describing the additive effects of risk factors on atherosclerosis. Phillips developed the concept of metabolic risk factors for myocardial infarction and described a cluster of abnormalities including glucose intolerance, hyperinsulinemia, hyperlipidemia, and hypertension [4,5]. In 1988, Reaven, an American endocrinologist, propounded that insulin resistance (IR) was the cause of glucose intolerance, hyperinsulinaemia, increased very-lowdensity lipoprotein cholesterol (VLDL-C), decreased high-density lipoprotein cholesterol (HDL-C) and hypertension and named the constellation of abnormalities "syndrome X" [6].…”
Section: Introductionmentioning
confidence: 99%